Forced Migration and Mortality in the Very Long Term: Did Perestroika Affect Death Rates Also in Finland? - SAARELA, JAN (Population Association of America, 2009)
In this article, we analyze mortality rates of Finns born in areas that were ceded to the Soviet Union after World War II and from which the entire population was evacuated. These internally displaced persons are observed during the period 1971–2004 and compared with people born in the same region but on the adjacent side of the new border. We find that in the 1970s and 1980s, the forced migrants had mortality rates that were on par with those of people in the comparison group. In the late 1980s, the mortality risk of internally displaced men increased by 20% in relation to the expected time trend. This deviation, which manifests particularly in cardiovascular mortality, coincides with perestroika and the demise of the Soviet Union, which were events that resulted in an intense debate in civil society about restitution of the ceded areas. Because state actors were reluctant to engage, the debate declined after some few years, and after the mid-1990s, the death risk again approached the long-term trend. Our findings indicate that when internally displaced persons must adjust to situations for which appropriate coping behaviors are unknown, psychosocial stress might arise several decades after their evacuation.